AFETIVIDADE NAS PRÁTICAS EDUCATIVAS: Uma análise desse processo de mediação no curso de Pedagogia - SANTOS, Magnucia Bezerra Soeiro dos (2024)
This research is part of the Research Line “Educational Institutions, Curriculum, Training and Teaching Work” of the Graduate Program in Education at UFMA, and addresses educational practices with a focus on affectivity. To this end, we conducted this study from the perspective of Vygotsky’s Historical-Cultural Theories and Henri Wallon’s Psychogenesis of the Whole Person based on the assumptions of Historical-Dialectical Materialism, as it allows the analysis of the object of study in its concreteness, materiality and historicity. Thus, it aims to analyze the educational practices of teachers in the Pedagogy course at UFMA, highlighting affectivity as an element that mediates the exercise of teaching. Therefore, the research has teachers as research participants and moves towards the procedures of a qualitative research conducted from bibliographic, documentary and empirical studies, based on authors such as: Vygotsky; Henri Wallon; Karl Marx; Engels; Saviani; Newton Duarte; Leontiev; Karel Kosik; Paulo Freire; Manacorda; and others. The results are organized into Units of Meaning, namely: conceptions of affectivity that mediate educational practices; affectivity in teaching planning and practice; and motivations for professional teacher training. However, we understand that affectivity is a relevant research topic for understanding the educational process since it points toward innovative possibilities and the training of pedagogues needs to be based on the subject in its entirety; therefore, developing a study on affectivity makes it possible to offer support to a teaching and learning process that considers not only cognition, but affectivity as a basic and essential element of education. This is because the research revealed to us that affectivity in typically human activities presupposes its undeniable presence in educational practices, allowing us to understand that affectivity is an important factor in the teaching-learning process. Such an impact can lead the student to establish a relationship of proximity or distance with the teaching objects, depending on the quality and intensity of the feelings involved in the process.